Trauma and Motherhood in Contemporary Literature and Culture
XII, 242 p.
Keywords: “A smart, innovative, and robust collection that offers a unique and important contribution to Motherhood Studies in its emphasis on trauma […] an important and emergent subfield of motherhood studies and one yet to be represented or developed through an edited collection.” —Andrea O’Reilly, Professor in the School of Gender, Sexuality, and Women’s Studies, York University, Canada “This volume breaks new ground by using trauma studies to shed light on certain less-studied experiences of pregnancy, birth, and motherhood.” —Valerie Heffernan, Professor of Literary and Cultural Studies and Head of the Maynooth University School of Modern Languages, Literatures and Cultures, Ireland Trauma and Motherhood in Contemporary Literature and Culture repositions motherhood studies through the lens of trauma theory by exploring new challenges surrounding conception, pregnancy, and postpartum experiences. Chapters investigate nine case studies of motherhood trauma and recovery in literature and culture from the last twenty years by exploring their emotional consequences through the lens of trauma, resilience, and “working through” theories. Contributions engage with a transnational corpus drawn from the five continents and span topics as rarely discussed as pregnancy denial, surrogacy, voluntary or involuntary childlessness, racism and motherhood, carceral mothering practices, surrogacy, IVF, artificial wombs, and mothering through war, genocide, and migration. Accompanied by an online creative supplement, this volume deals with silenced aspects of embodied motherhood while enhancing a better understanding of the cathartic effects of storytelling. Laura Lazzari is a Scientific Collaborator at the Sasso Corbaro Foundation for the Medical Humanities, Switzerland, and a Research Scholar at the Catholic University of America, USA. She specializes in Motherhood Studies and the Medical Humanities and has published extensively on women’s writing in the Italian-speaking world. Nathalie Ségeral is Lecturer in French at the University of Sydney, Australia, and Associate Professor of French at the University of Hawaii at Mānoa, USA. She specializes in Holocaust, genocide, memory and feminist studies, trauma theory, and the Francophone South Pacific.